ANALISIS PERMINTAAN DAN PENAWARAN UANG PENDEKATAN PERSAMAAN SIMULTAN (STUDI KASUS INDONESIA TAHUN 2000.1- 2004.4) - Basuki, Agus Tri (Jurnal Ekonomi & Studi Pembangunan, 2006)
This research analyze about money demand and supply function in 2000.1 to 2004.4 by simultaneous equation approach. From the derivative of money demand equation, we can conclude that the money demand influenced by Gross Domestic Product (GDP) positively and by the exchange rate negatively. By derivating money supply equation, we can conclude that money demand influenced by GDP negatively and by Consumer Price Index positively